Comparison of the epifaunal assemblage of an invasive and native macroalga - Brunner, Benedikt P. (2021)
The rapid spread of introduced seaweeds is of essential concern, as they can have a deleterious impact on coastal native seaweed and seagrass communities. However, non-indigenous species can generate mixed responses when introduced to native assemblages, and increase habitat complexity, depending on the spatial and ecological context. By taking advantage of the cooccurrence of the native Ulva seaweeds and the non-native Agarophyton vermiculophyllum in the Clonakilty estuary (Cork, Ireland) we aim to assess the differences of the epifaunal community of the native and invasive macroalgal species and how epifaunal biodiversity may be affected by the invasive. In four locations over four sampling occasions, a total of 253 quadrants of algae and epifaunal biomass were sampled. The Ulva dominated sections mainly contained macroalgae with tubular morphotypes and some sporadic patches of laminar Ulva rigida. The average algal biomass of both species was similar, however, the biomass of the red seaweed was highly variable throughout the seasons. The native algal canopy hosted up to four times more epifaunal biomass compared to the invasive rhodophyte. Moreover, the epifaunal community of both canopies differed substantially, whereas deposit-feeding organisms had a higher abundance in Ulva spp. canopies and the carnivorous crab, Carcinus maenas, was much more abundant in A. vermiculophyllum samples. The native green macroalgae hosted more invertebrate taxa, however no difference in biodiversity was found. Increased predation on deposit-feeders and grazers, as well as, the structural and chemical resistance of A. vermiculophyllum against grazing and overgrowth by epiphytes may reduce the trophic transfer from primary production toward higher trophic levels.